Myricetin protects against doxorubicin-induced acute kidney injury in rats by mitigating oxidative damage and apoptotic response - Karadogan, Muhammed Talha; Cicek, Betul; Cinisli, Kagan Tolga; Mendil, Ali Sefa; Ozkaraca, Mustafa; Yilmaz, Furkan; Suleyman, Halis (Frontiers in Pharmacology, 2025)
IntroductionDoxorubicin (DOX) is a potent anti-neoplastic agent widely preferred in treating various tumors. However, DOX’s off-target toxicity in healthy tissues, such as nephrotoxicity, limits its clinical utilization. DOX generates oxidative stress and apoptosis in the kidneys, which stimulates cytotoxic cellular signaling. Myricetin (MYC), an important natural flavonoid, exhibits antioxidant and antiapoptotic features. In this regard, the current report was designed to explore the renoprotective potential of MYC on DOX-induced nephrotoxicity.MethodsAnimals were divided into four groups with six rats in each group: control, MYC, DOX, MYC + DOX. MYC was given orally to rats at 100 mg/kg for 10 days and DOX was injected intraperitoneally as a single dose of 20 mg/kg on the eighth day. Serum samples were evaluated for creatinine and blood urea nitrogen (BUN), and histopathological analysis of the kidneys was conducted. The levels of malondialdehyde (MDA), myeloperoxidase (MPO), total oxidant status (TOS), glutathione (GSH), glutathione peroxidase (GPx), and total antioxidant capacity (TAC) were measured in the renal tissues. Additionally, biochemical assessments of Bax and Bcl-2 proteins, along with immunohistochemical evaluations of the expression levels of caspase-3 and apoptosis-inducing factor (AIF), were conducted to evaluate apoptosis.ResultsPre-treatment of MYC decreased DOX-elicited elevation in creatinine and BUN levels (p < 0.05). Histopathological findings demonstrated the nephroprotective role of MYC on renal damage (p < 0.05), which was in harmony with the biochemical findings. Furthermore, MYC demonstrated antioxidant properties by reversing the increase in MDA, TOS, and MPO levels and the decrease in GSH, GPx, and TAS levels caused by DOX (p < 0.05). MYC pre-treatment also markedly prohibited DOX-induced elevation of Bax level, and rise of expression of caspase-3 and AIF, and reduction of Bcl-2 levels (p < 0.05).ConclusionIt could be supposed that the nephroprotective role of MYC towards DOX-induced kidney damage might be mediated by its antioxidant and antiapoptotic features.